2011
DOI: 10.1007/s10714-011-1185-7
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal frequencies of asymptotically flat two-dimensional black holes

Abstract: We discuss whether the minimally coupled massless Klein-Gordon and Dirac fields have well defined quasinormal modes in single horizon, asymptotically flat two-dimensional black holes. To get the result we solve the equations of motion in the massless limit and we also calculate the effective potentials of Schrödinger type equations. Furthermore we calculate exactly the quasinormal frequencies of the Dirac field propagating in the two-dimensional uncharged Witten black hole. We compare our results on its quasin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 46 publications
(136 reference statements)
2
33
0
Order By: Relevance
“…In a similar way to [42], we see that for asymptotically anti-de Sitter two-dimensional black holes the massless Klein-Gordon equation simplifies to a free Schrödinger type equation (see Eqs. (25) and (26) in [42]), and since its solutions do not satisfy the boundary conditions of the QNM, we find that the massless Klein-Gordon field does not have well defined QNF in asymptotically anti-de Sitter two-dimensional black holes.…”
Section: Quasinormal Frequencies Of the Klein-gordon Fieldmentioning
confidence: 62%
See 4 more Smart Citations
“…In a similar way to [42], we see that for asymptotically anti-de Sitter two-dimensional black holes the massless Klein-Gordon equation simplifies to a free Schrödinger type equation (see Eqs. (25) and (26) in [42]), and since its solutions do not satisfy the boundary conditions of the QNM, we find that the massless Klein-Gordon field does not have well defined QNF in asymptotically anti-de Sitter two-dimensional black holes.…”
Section: Quasinormal Frequencies Of the Klein-gordon Fieldmentioning
confidence: 62%
“…Becar et al [39] compute exactly the QNF of the Klein-Gordon field minimally coupled to scalar curvature in the uncharged Witten black hole [43,44] (see also [40]). For this black hole, also Becar et al [41] calculate exactly the QNF of the massless Dirac field and in [42] these results are extended to the massive Dirac field. Furthermore in the last reference it is shown that in asymptotically flat two-dimensional black holes the massless Klein-Gordon and Dirac fields do not have well defined QNM and hence the frequencies calculated in [41] cannot be QNF of the massless Dirac field in the uncharged Witten black hole.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations